2022
DOI: 10.1021/jacs.2c05660
|View full text |Cite
|
Sign up to set email alerts
|

Electrochemical Upgrading of Formic Acid to Formamide via Coupling Nitrite Co-Reduction

Abstract: Formic acid (HCOOH) can be exclusively prepared through CO2 electroreduction at an industrial current density (0.5 A cm–2). However, the global annual demand for formic acid is only ∼1 million tons, far less than the current CO2 emission scale. The exploration of an economical and green approach to upgrading CO2-derived formic acid is significant. Here, we report an electrochemical process to convert formic acid and nitrite into high-valued formamide over a copper catalyst under ambient conditions, which offer… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
90
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 107 publications
(90 citation statements)
references
References 46 publications
0
90
0
Order By: Relevance
“…Additionally, if *COOH is the key intermediate for forming the first C–N bond during coreduction of NO 2 – and CO 2 , it is likely that the electrochemical coreduction of NO 2 – and HCOOH would result in better urea synthesis performance compared to the reduction system of NO 2 – and CO 2 . To verify this mechanism, control experiments such as the coreduction of HCOOH and NO 2 – , combined with in situ ATR-FTIR analysis, may be conducted . Despite the fact that urea was not detected during the electrochemical coreduction of CO+NO 2 – , it is still possible that other C–N coupling products (such as methylamine, formamide, ethylamine, , and so on) could be formed.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Additionally, if *COOH is the key intermediate for forming the first C–N bond during coreduction of NO 2 – and CO 2 , it is likely that the electrochemical coreduction of NO 2 – and HCOOH would result in better urea synthesis performance compared to the reduction system of NO 2 – and CO 2 . To verify this mechanism, control experiments such as the coreduction of HCOOH and NO 2 – , combined with in situ ATR-FTIR analysis, may be conducted . Despite the fact that urea was not detected during the electrochemical coreduction of CO+NO 2 – , it is still possible that other C–N coupling products (such as methylamine, formamide, ethylamine, , and so on) could be formed.…”
Section: Discussionmentioning
confidence: 99%
“…To verify this mechanism, control experiments such as the coreduction of HCOOH and NO 2 – , combined with in situ ATR-FTIR analysis, may be conducted . Despite the fact that urea was not detected during the electrochemical coreduction of CO+NO 2 – , it is still possible that other C–N coupling products (such as methylamine, formamide, ethylamine, , and so on) could be formed.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…When looking at the amino acid synthesis, seven of them have been electrochemically synthesized from α-keto acids (including pyruvate) and NH2OH using a TiO2 catalyst at low pH and relatively positive potential (-320 mV vs. SHE) [64] (Figure 5, reactions On the other hand, formamide is considered as the first building block in many prebiotic syntheses [68]. Electrochemical synthesis of formamide and acetamide have been demonstrated from mixtures of formate or acetate and nitrite at -0.4V vs. SHE on Cu catalyst, in conditions easily retrieved in hydrothermal context [63] (Figure 5, reactions 5). This formamide and acetamide could then react with other carbon-based molecules to produce amino acids, nucleobases and lipid precursors.…”
Section: Amino Acids Synthesis Amino Acids Synthesis Carbonyl Branchmentioning
confidence: 99%
“…In this regard, a plethora of research has focused on the development of effective catalysts to improve the selectivity and Faradic e ciency (FE) of NH 3 or aimed at studying intrinsic mechanisms by exploring new characterization techniques [1][2][3][4][5][6][7][8] . Excitingly, as a sustainable alternative to traditional thermal and enzymatic catalysis, coupling inorganic nitrogen sources (e.g., nitrogen (N 2 ), NO 3 − , NO 2 − ) and carbon sources (e.g., carbon dioxide, carbon monoxide, and other carbonyl substrates) to form upgraded organic amines is becoming a rapidly emerging area of electrocatalytic C − N bond construction, pushing NO 3 − /NO 2 − electroreduction to a new level due to the frequent invocation of C − N construction in synthetic chemistry [9][10][11][12][13][14][15] . For example, Wang et al reported electrocatalytic C − N coupling to successfully synthesize methylamine from CO 2 and NO 3 − catalyzed by a well-designed molecular cobalt catalyst.…”
Section: Introductionmentioning
confidence: 99%